Building Communities: College Preparation Education for Grandparents Raising Grandchildren. Issue 1 (2nd January 2016) - Bertram, Anita Glee; Sears, Kaye; Burr, Brandon; Fuller, Jenifer; Green, Katheryn
ABSTRACT: Nationwide about 4.2 million households have grandparents and grandchildren co-residing. Of those homes, 67% showed the grandparent(s) as the householder(s) (Current Population Survey, 2012). In Oklahoma, 100, 213 children under age 18 live in a home headed by grandparents or other relatives (U.S. Census Bureau, 2010). Nearly 80, 000 children live with grandparents as heads of the household (U.S. Census Bureau, 2010). Typically, children raised by grandparents do not attend college. Two college preparatory trainings for grandparents and adolescent children were held on university campuses. Grandparents and grandchildren were given student-led tours of the campus, financial aid information, information about careers and how to work with school counselors, and information about the state's free tuition incentive program. Pre- and posttests were used to assess changes in awareness of both grandparents and grandchildren of college opportunities and information. Follow-up focus groups were conducted with participants.